On the direction of transcription of cloned genes in Neurospora crassa. - S. M. Pietschmann; J. Eberle; T. Sommer; V. E. A. Russo (Fungal Genetics Reports, 1989)
On the direction of transcription of cloned genes in Neurospora crassa.